MECHANICAL PROPERTIES OF WOOD PLASTIC COMPOSITES WITH THE ACTIVATED WOOD FILLER (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The aim of the research was a study of the effect of activation of birch sawdust microparticles with a dilute solution of sodium hydroxide at a low temperature on mechanical properties and water sorption of the obtained wood plastic composite (WPC) samples obtained from a by-product of a domestic wood mechanical processing and a recycled polymer municipal waste. It was found that the mechanical (tensile, bending) properties of the WPC samples filled with the activated birch sawdust microparticles were higher than those of the samples filled with the initial sawdust. The sorption and swelling degree of the WPC samples with the activated filler were lower than those for the samples with the initial sawdust. However, the difference in the values of the water sorption and the swelling degree for the samples filled with the activated and initial wood microparticles were relatively low in comparison with the observed essential difference in their mechanical properties. This fact was explained by the enhanced content of carbonyl groups in the activated sawdust microparticles that are able to absorb water.